Under the midnight sun - Higashino, Keigo, 1958- (Minotaur Books, 2025)
In an abandoned building in 1973 in Osaka, the body of a murdered man is found. Working quietly and methodically, Detective Sagasaki discovers two people who appear to have clear links to the crime -- Ryo, the uncommunicative son of the dead man, and Yukiho, the charming daughter of the man principally in the frame for the murder. Decades pass. The murder remains unsolved. Ryo and Yukiho continue with their lives, disappearing and reappearing through school, jobs, and marriage. But Sagasaki, who carries tenaciousness to the point of obsession, is prepared to spend as much time as it takes to solve an insoluble case. As the many strands of plot, coincidence, and rumor dovetail, Sagasaki zeroes in on the curious bond connecting Yukiho to Ryo. Journey under the Midnight Sun isn't a whodunnit or even a whydunnit, but a what-exactly-is-being-dunnit, and an extraordinary work of fiction that could be read as a potted history of Japan, an exploration of a crumbling social order, a ludic literary puzzle that plays with genre expectations, and most of all, a tantalising mystery that keeps the pages turning. --